الخصائص السيكومترية لمقياس التوافق النفسي لدى الأطفال ذوي اضطراب الكلام واللغة - هيبة، حسام إسماعيل; البسيوني، سماح محمد (جامعة عين شمس - مركز الإرشاد النفسي, 2023)
هدفت الدراسة التحقق من الخصائص السيكومترية لمقياس التوافق النفسي لدى عينة من الأطفال ذوي اضطراب الكلام واللغة، وتكونت عينة الدراسة من (۱۰۰) طفل وطفلة من ذوي اضطراب الكلام واللغة المترددين على مستشفى دار الشفاء بمدينة المحلة الكبرى محافظة الغربية، واستخدمت الدراسة الأساليب الإحصائية التالية : التحليل العاملي، معامل الارتباط، معامل ألفا كرونباخ. وأسفرت نتائج التحليل العاملي عن ثلاثة عوامل (التوافق الشخصي، التوافق الأسري، التوافق المدرسي)، وأكدت النتائج على صدق وثبات المقياس. The study aimed to verify the Psychometric Characteristics of the psychological adjustment scale in a sample of children with speech and language disorders, and the study sample consisted of (100) children with speech and language disorders who frequented Dar Al Shifa Hospital in El Mahalla El Kobra, Gharbia Governorate, The researcher used the following statistical methods: Factor analysis, Correlation Coefficient, Cronbach's alpha. The results of the factor analysis showed three factors (personal adjustment, family adjustment, school adjustment), and the results confirmed the validity and consistency of the scale.
Keywords: اضطراب الكلام -- التوافق النفسي -- الذكاء الروحي -- العنف الأسري